Development of SMASH Skills Training Model on Volleyball Based on Interactive Multimedia - Suhairi, Muhammad; Asmawi, Moch.; Tangkudung, James; Hanif, Achmad Sofyan; Dlis, Firmansyah (International Journal of Interactive Mobile Technologies (iJIM), 2020)
— SMASH’s skill is a technique that can be done by a person in a hard swooping towards your opponent to produce numbers. Interactive multimedia technology is expected to be a guideline for athletes in looking at more variation models of SMASH. The aim of development research is to produce an interactive multimedia volleyball playing skill training model. The method used in this research is development research design by Borg and Gall. The approach used in this study is a qualitative and quantitative approach. This study is hoped to improve volleyball skills by looking at the interactive multimedia volleyball playing practice model. This study concludes that interactive multimedia-based volleyball skill playing model can be used in the actual application of exercises.